Genetic Polymorphism of Drug Metabolic Gene CYPs, VKORC1, NAT2, DPYD and CHST3 of Five Ethnic Minorities in Heilongjiang Province, Northeast China - Zhang T; Li Q; Dong B; Liang X; Jia M; Bai J; Yu J; Fu S (Dove Medical Press, 2021)
Tingting Zhang,1,2,* Qiuyan Li,1- 3,* Bonan Dong,1,2 Xiao Liang,1,2 Mansha Jia,4 Jing Bai,1,2 Jingcui Yu,2,4 Songbin Fu1,2 1Laboratory of Medical Genetics, Harbin Medical University, Harbin, People's Republic of China; 2Key Laboratory of Preservation of Human Genetic Resources and Disease Control in China (Harbin Medical University), Ministry of Education, Harbin, People's Republic of China; 3Editorial Department of International Journal of Genetics, Harbin Medical University, Harbin, People's Republic of China; 4Scientific Research Centre, The Second Affiliated Hospital of Harbin Medical University, Harbin, People's Republic of China*These authors contributed equally to this workCorrespondence: Songbin Fu; Jingcui Yu Email fusb@ems.hrbmu.edu.cn; yujingcui@ems.hrbmu.edu.cnIntroduction: Genetic variability in genes encoding drug-metabolizing enzymes may contribute to the heterogeneity of drug responses in different populations. Extensive research in pharmacogenomics in major populations around the world provides us with a great deal of information about drug-related genetic polymorphisms.Objective: The purpose of this study was to detect the genetic variation of drug-metabolism-related genes in the five ethnic minorities Daur, Hezhen, Ewenki, Mongolian and Manchu in China, and to analyze the distribution differences among ethnic groups.Methods: We genotyped 32 SNPs of drug metabolism genes in 882 healthy Chinese volunteers from five ethnic groups. The genotype frequency and allele frequency of the five ethnic groups were calculated, and the different variants among the five ethnic groups were compared by chi-square test. Genetic parameters were analyzed using Popgene software. The genetic structure of five ethnic minorities was analyzed by principal component analysis, and compared with 26 populations.Results: We found that SNPs of genes related to drug metabolism existed diversity in different populations. Among them, rs8192766 and rs9419082 in CYP2E1 showed statistical differences between Daur and Manchu, and NAT2 rs1801280 showed statistical differences between Hezhen and Mongolian. In addition, the five populations we studied had the smallest differences with EAS populations. There was haplotype diversity in CHST3, VKORC1, CYP1A2 and CYP2E1 genes in the five ethnic minorities, and these haplotype polymorphisms were related to the use of corresponding drug doses. Cluster analysis shows that the five ethnic minorities in Heilongjiang Province are clustered together with the EAS populations.Conclusion: These results suggest that understanding the diversity of drug-related genetic markers is critical for individualized drug gene therapy programs in ethnic minorities in China as well as in populations highly mixed with these ethnic groups.Keywords: pharmacogenomics, population genetic, single nucleotide polymorphism, Chinese minorities